“He Was Such a Block of Ice.” Interpretative Phenomenological Analysis of Adolescent Girls’ Work in an Intimate Relationship - Kacprzak-Wachniew, Kamila; Spychalska-Stasiak, Justyna (Qualitative Sociology Review, 2024)
The first romantic relationships of adolescents are of significant developmental importance, and the acquired experience is a cultural issue. The study aimed to capture what meanings young teenagers give their first love experiences. In-depth interviews were conducted with six teenage girls. A detailed idiographic analysis, based on Interpretative Phenomenological Analysis (IPA), allowed us to present the work of adolescents to maintain intimacy and ensure the stability of a romantic relationship. It was noticed that young girls take an emotionally leading role in their romantic relationships, feel responsible for them, and act following the stereotypical gender order. The interpretative framework adolescents adopt may result from therapeutic and utilitarian narratives, addressed mainly to women.